2018
DOI: 10.1097/mcg.0000000000000842
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hepatitis B Virus Infection and Pregnancy Outcomes

Abstract: Maternal HBsAg carriage was associated with several adverse pregnancy outcomes. Furthermore, hepatitis B viral activity in pregnancy might have certain effects on pregnancy outcomes. Careful surveillance of maternal HBsAg status as well as viral activity in the second trimester among HBsAg carriers is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 31 publications
1
35
1
1
Order By: Relevance
“…We found that women with HBsAg positive status were tended to be slightly older than women with HBsAg negative status. This result is consistent with those of other studies, which also showed that women infected with the hepatitis B virus were more likely to be older [15][16][17]. Moreover, there is evidence that the number of abnormal blood glucose cases during pregnancy is higher among those with an HBsAg positive status than among those with an HBsAgnegative status.…”
Section: Discussionsupporting
confidence: 92%
“…We found that women with HBsAg positive status were tended to be slightly older than women with HBsAg negative status. This result is consistent with those of other studies, which also showed that women infected with the hepatitis B virus were more likely to be older [15][16][17]. Moreover, there is evidence that the number of abnormal blood glucose cases during pregnancy is higher among those with an HBsAg positive status than among those with an HBsAgnegative status.…”
Section: Discussionsupporting
confidence: 92%
“…Cui et al (7) reported that miscarriage (but not stillbirth) was significantly associated with maternal HBV status when compared to HBV-negative mothers. Miscarriage and stillbirth are usually caused by other negative outcomes during pregnancy, which include pregnancyinduced hypertension, fetal distress, and macrosomia (14).…”
Section: Discussionmentioning
confidence: 99%
“…Our study had several limitations, most importantly the relatively small sample size along with several relatively rare outcomes. Other studies previously assessed other factors such as gestational diabetes, pre-eclampsia, and placental abruption, which we were unable to evaluate (10,14).…”
mentioning
confidence: 84%
“…There are studies which have showed severe adverse pregnancy outcome in HBsAg positive mothers and warrant a careful surveillance of maternal HBsAg status and viral activity especially in second trimester. 13…”
Section: Discussionmentioning
confidence: 99%